2020
DOI: 10.3390/molecules25143167
|View full text |Cite
|
Sign up to set email alerts
|

Application Research of Biochar for the Remediation of Soil Heavy Metals Contamination: A Review

Abstract: Soil contamination by heavy metals threatens the quality of agricultural products and human health, so it is necessary to choose certain economic and effective remediation techniques to control the continuous deterioration of land quality. This paper is intended to present an overview on the application of biochar as an addition to the remediation of heavy-metal-contaminated soil, in terms of its preparation technologies and performance characteristics, remediation mechanisms and effects, and impacts on heavy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(45 citation statements)
references
References 124 publications
3
42
0
Order By: Relevance
“…While at the plant level, the application of slag-based fertilizers causes an increase in the antioxidant defense system and causes a reduction in the translocation of PTEs to plant shoots. However, the mechanisms for PTE ion remediation by slag are similar to many other applied amendments in previous studies, such as lime [88], biochar [89][90][91][92], zeolite [93], chitosan [94], the indigenous strain Bacillus XZM [95], hydrogen sulfide [96], and sepiolite [97]. The basic PTE ion immobilization on the slag surface was attributed to the presence of silicate, ferrites, and calcium oxides on the surface [98].…”
Section: Mechanism Of Slag Interaction With Potentially Toxic Elements In Soilsupporting
confidence: 63%
“…While at the plant level, the application of slag-based fertilizers causes an increase in the antioxidant defense system and causes a reduction in the translocation of PTEs to plant shoots. However, the mechanisms for PTE ion remediation by slag are similar to many other applied amendments in previous studies, such as lime [88], biochar [89][90][91][92], zeolite [93], chitosan [94], the indigenous strain Bacillus XZM [95], hydrogen sulfide [96], and sepiolite [97]. The basic PTE ion immobilization on the slag surface was attributed to the presence of silicate, ferrites, and calcium oxides on the surface [98].…”
Section: Mechanism Of Slag Interaction With Potentially Toxic Elements In Soilsupporting
confidence: 63%
“…Bio-char has received more attention in recent years, and several reviews have summarized its production [ 101 , 154 157 ]. Bio-char presents porous structure, abundant functional groups, high surface area, which includes minerals and trace metals [ 158 ], so it shows a wide range of applications, including adsorption (chemical substances [ 159 , 160 ], dye [ 161 , 162 ], and heavy metals [ 17 , 163 , 164 ]), catalysis [ 165 168 ], soil repair [ 163 , 169 ], and use as building materials [ 170 ], electrochemical energy storage [ 171 173 ], etc. During the process of bio-oil or bio-char production, syngas containing hydrogen, carbon monoxide, methane, etc.…”
Section: Products Derived From Plant Biomassmentioning
confidence: 99%
“…Studies have shown that use of organic materials that have high pH, CEC, surface area, and porosity such as biochar can ameliorate contaminated soil due to their efficiency at adsorbing HMs from soils (Table 3), [20,115,134]. Field and greenhouse studies have shown that application of biochar increased plant growth and reduced the uptake of HMs [6,74,135,136].…”
Section: Impact Of Biochar On Soils Contaminated With Heavy Metals (Hms)mentioning
confidence: 99%